Automated regional citrate anticoagulation system based on individualized dosing models in nonliver failure patients undergoing PIRRT therapy - Qi Zhang; Damin Ding; Chaobin Wang; Jianxin Lu; Qin Zhu; Feng Ding (Renal Failure)
Introduction Regional citrate anticoagulation is a preferred option for renal replacement therapy in critically ill patients. However, current implementations ignore individual differences that may exist in the fluctuation of patients’ ionized calcium levels. To address this problem, individualized citrate and calcium supplementation models were established based on the pharmacokinetic and clearance characteristics of citrate, and an automated regional citrate anticoagulation system was built with these models as its core to facilitate the treatment of clinical patients. This study was designed to preliminarily evaluate the safety and efficacy of this system, the SuperbMed® RCA-SP100 automated regional citrate anticoagulation system, in prolonged intermittent renal replacement therapy.Methods Seven patients undergoing prolonged intermittent renal replacement therapy completed treatment with the SuperbMed® RCA-SP100 system. In vivo and in vitro ionized calcium levels were measured every hour before and after the start of dialysis. The accuracy and alarm sensitivity of the pumps were also monitored.Results During seven treatments, the average extracorporeal ionized calcium level was 0.34 ± 0.02 mmol/L, and the mean ionized calcium level in vivo was 1.09 ± 0.07 mmol/L. No patient required intervention, and there was no filter coagulation. The pumps all had an absolute accuracy less than 5%, and alarms could be triggered precisely.Conclusions We reported on an automated system that allows for individualized citrate and calcium supplementation in prolonged intermittent renal replacement therapy and enables the precise and secure implementation of regional citrate anticoagulation.